Listening to you… i find myself: bibliotherapy experience (PPA) - Castro León, Mónica María (2020)
It proposes to reflect on the constitution of our identity. Questions as Who are we? They give place to the encounter of the subject within the social fabric, in a permanent journey. Where the outside and inside concepts show their reversible character. Ancestral and familiar stories are heard, that they tell us. In front of which we made our own saying entailing a different task. We propose a psycho-social-emotional technique of Bibliotherapy applied to PPA. Focused on the story and the storyteller. The story with its valuable power to think, and to think oneself. From the projective screen that it implies. How the knowledge of the world, through the thoughts, feelings and actions that proposes with its plot and characters. Expanding the knowledge of the other, of the world, of the human psyche. And a narrator, who from a healthy bond, repairs the relationship with his community. Making resilience more viable.